2012
DOI: 10.5194/isprsannals-i-4-251-2012
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Lidar and Volunteered Geographic Information to Map Flood Extents and Inundation

Abstract: ABSTRACT:Floods are one of the most destructive natural disasters that threaten communities and properties. In recent decades, flooding has claimed more lives, destroyed more houses and ruined more agricultural land than any other natural hazard. The accurate prediction of the areas of inundation from flooding is critical to saving lives and property, but relies heavily on accurate digital elevation and hydrologic models. The 2011 Brisbane floods provided a unique opportunity to capture high resolution digital… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(26 citation statements)
references
References 13 publications
0
25
0
1
Order By: Relevance
“…In the area of flood management, Alfonso et al () tested a system in which citizens sent their reading of water level rulers by text messages. Since then, other studies have adopted similar approaches (Lowry & Fienen, ; McDougall, ; McDougall & Temple‐Watts, ) and have adapted them to new technologies, such as website upload (Degrossi et al, ; Starkey et al, ). Kutija et al () developed an approach in which images of floods are received, from which water levels are extracted.…”
Section: Review Of Crowdsourcing Data Acquisition Methods Usedmentioning
confidence: 99%
See 1 more Smart Citation
“…In the area of flood management, Alfonso et al () tested a system in which citizens sent their reading of water level rulers by text messages. Since then, other studies have adopted similar approaches (Lowry & Fienen, ; McDougall, ; McDougall & Temple‐Watts, ) and have adapted them to new technologies, such as website upload (Degrossi et al, ; Starkey et al, ). Kutija et al () developed an approach in which images of floods are received, from which water levels are extracted.…”
Section: Review Of Crowdsourcing Data Acquisition Methods Usedmentioning
confidence: 99%
“…For example, Jongman et al () combined near‐real‐time satellite data with near‐real‐time Twitter data on the location, timing, and impacts of floods for case studies in Pakistan and the Philippines for improving humanitarian response. McDougall and Temple‐Watts () combined high quality aerial imagery, LiDAR data, and publically available volunteered geographic imagery (e.g., from Flickr) to reconstruct flood extents and obtain information on depth of inundation for the 2011 Brisbane floods in Australia.…”
Section: Review Of Crowdsourcing Data Acquisition Methods Usedmentioning
confidence: 99%
“…Multi-source satellite and Twitter data were combined to delineate the flood extent on a daily basis [33]. Similar studies can also be found in [34][35][36][37][38]. These studies showed that social media data is valuable in providing disaster-related information at locations that are not being sensed by satellite sensors.…”
Section: Introductionmentioning
confidence: 54%
“…Nedkov and Zlatanova performed a shortest-path calculation using crowdsourced data about infrastructure health [16]. Roche and Propeck-Zimmermann discussed the method and issues involved in using VGI to support crisis management [17], harnessing VGI to build and update SDI [18,19]. Mooney and Corcoran [20] described the potential for using VGI in health computing applications.…”
Section: Related Workmentioning
confidence: 99%